“How Are My Age and Cows Related?” Cognitive Interviewing as a Tool to Pretest Survey Questions in Two Limited Resource Settings - Wenemark, Marika; Ngwili, Nicholas; Ndoboli, Dickson; Wieland, Barbara; Roesel, Kristina (Frontiers in Veterinary Science, 2022)
Antimicrobial resistance is a complex topic requiring interdisciplinary solutions embedded in One Health thinking. Currently, many surveys are underway in low- and middle-income countries to study how antimicrobial use in the livestock sector is driving resistance. In a survey, the respondents must understand and answer the questions correctly to produce accurate and valuable results. Pretesting survey questions is therefore important but sometimes not performed due to limited time and resources. Cognitive interviewing is a pretesting method to give insights into the respondent's way of interpreting and mentally processing the survey questions to identify problems and finding ways to improve the questions. It has previously been suggested that cognitive interviews may be difficult to use in some cultural settings. This study aimed to use cognitive interviews in a respondent-adjusted way to study how survey questions related to antimicrobial use are understood and answered by 12 small-scale farmers in Kenya and Uganda. The results show that even a small number of interviews and using interviewers with limited knowledge of cognitive interviewing can identify many problems in survey questions and the survey tool. Cognitive interviews may provide a feasible and affordable way of pretesting questionnaires in situations where time and resources are limited, for example, during a disease outbreak.